The Role of Business Management in the Innovative Development of the Cultural Tourism and Education Industry - Yang, Yaqin (Transactions on Economics, Business and Management Research, 2024)
As China’s comprehensive strength continues to grow, along with the rapid development of information technology, new opportunities have emerged for the development of the cultural tourism and education industry. With an increasing demand for cultural tourism and lifelong learning, this industry is facing unprecedented development opportunities. The market size is continuously expanding, and the range of cultural tourism and education products and services is becoming more diverse, meeting the needs of various consumer groups. Innovation has become mainstream; companies and institutions within the industry are constantly exploring new development models, which promote the transformation and upgrading of the cultural tourism and education industry. Increased policy support has provided a solid guarantee for the innovative development of this industry. Thus, in the process of formulating operational strategies, it is essential to first conduct an in-depth market analysis to understand consumer needs, competitive situations, and industry trends. Subsequently, product strategies that align with market laws should be developed, including product positioning, unique feature creation, and the enhancement of product lines. Simultaneously, a reasonable pricing strategy must be established to ensure that product pricing is competitive while achieving the profit goals of the enterprise. Through the formulation and implementation of these strategies, business management can help the cultural tourism and education industry achieve sustainable development.